Biotechnological methods as a tool for efficient sugar beet breeding - T. P. Zhuzhzhalova; E. O. Kolesnikova; E. N. Vasilchenko; N. N. Cherkasova (Вавиловский журнал генетики и селекции)
Here we consider aspects of the application of biotechnological methods to rapid creation, propagation, and maintenance of plants with improved or new traits in sugar beet breeding. The results of the works carried out in these fields by the Federal State Budgetary Scientific Institution "The A.L. Mazlumov All-Russia Research Institute of Sugar Beet” are reviewed. A close association between morphological and physiological changes in in vitro cultured organs and tissues, on the one hand, and breeding traits, on the other hand, which allows the development of experimental systems for non-amphimictic plant reconstruction is shown. The influence of in vitro growth conditions on haploid cells of unfertilized sugar beet ovules in the course of obtaining doubled haploid lines with high degree of homozygosity and maintenance of valuable breeding properties is considered. As compared to common inbreeding, this method shortens the time for development of homozygous material from 10-12 to 3-5 years, which is of great importance for speeding-up the breeding process. The results of studies on the culturing of mature sugar beet zygotic embryos based on in vitro selective systems have made it possible to improve the adaptive potential of plants and to provide complex resistance to environmental stress factors. Strict selection under abiotic stress conditions allowed creation of sugar beet isogenic lines with tolerance of drought, salinity, and soil acidity. It is shown that the proposed original design of mass-scale microclonal in vitro reproduction and deposition of elite plants as components of highly productive hybrids can be used to obtain seeds of uniform high-quality breeding material. The technologies developed by biotechnological methods are a topical and innovative direction of inquiry, since the application of these techniques to sugar beet breeding will promote obtaining of competitive hybrids with a set of commercially valuable traits. The combination of biotechnology methods, including tissue culture, and traditional breeding techniques is expected to provide an opportunity to obtain a new starting material to develop domestic varieties and hybrids of new generation with heterosis effect and a wide resistance spectrum persisting across generations.